THE EUROPEAN COMPANY (SOCIETAS EUROPAEA) ON RIND SIGHT - Niminet, Liviana Andreea (Studies and Scientific Researches. Economics Edition, 2016)
The article deals with the rind aspects of European Company (also known by its Latin name Societas Europaea or SE), a “type of public limited-liability company regulated under European Union law”. Although this form of company was proposed more than 40 years ago, it was only in 2001 when the Council issued Regulation (EC) No 2157/2001 of 8 October 2001 on the Statute for a European company defining the European company (SE) as “a legal structure that permits a company to operate in different European Union (EU) countries under a single statute”, as determined by the law of the Union and common to all EU countries. Being a new legal form, the SE coexists with the corporate forms that already were in each Member Statebeing governed by both European Regulation and national law. As it follows we address the rules, classification, conditions for settling an SE, organization structures, tax harmonization, employee involvement in the SE, advantages and disadvantages of SEs, as well as the opportunity of SPEs.